An Empirical Model on Customers' Perception in the Selection of Indian Prepaid Mobile Services - Rajeswari, P. S.; Ravilochanan, P. (Indian Journal of Finance, 2014)
India, a leading country in the telecommunication sector, has shown remarkable growth in prepaid mobile subscriptions through rigorous rural penetration. At the same time, the rate of monthly customer attrition is very high when compared with other countries across the globe. Customer churn is very aggressive, particularly in the prepaid segment, when compared with the postpaid segment. Hence, it is decidedly imperative for the mobile operators to comprehend the exact preferences of the customers to select the mobile operators based on prepaid mobile services attributes. Thus, the purpose of the present paper was to examine the reasons for the customers to select specific service providers and to develop a business model based on the operational strategies for the prepaid mobile segment. Descriptive research method was adopted for the present study, and by using a structured questionnaire, the survey method was undertaken. A total of1102 sample respondents from 10 cities across Tamil Nadu participated in the study (using purposive sampling method). The factors related to technology based customer care services, accessibility, roaming charges, network coverage, and call charges were found to be acting as drivers for the customers to select a specific service provider. Based on this analysis, an empirical business model was designed by integrating the respective marketing elements and operational key areas to improve the business portfolio of the mobile service providers. Finally, operational strategies were recommended based on the current market scenario.